VARIABLE RESPONSE TO INHALED NITRIC OXIDE IN POSTOPERATIVE PATIENTS OF MITRAL STENOSIS WITH PULMONARY HYPERTENSION - Razzaq, Zubia; Aslam, Muhammad; Hussain, M Mazhar; Naqvi, Shahab; Zameer, Muhammad; Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 2009)
Background: This study was carried out to determine the vasodilator response of inhaled nitric oxide in patients with pulmonary hypertension (PH) after valve replacement surgery for mitral valve disease. Method: This Quesi experimental study was carried out at the intensive care unit of Armed Forces Institute of Cardiology (AFIC) in collaboration with Department of Physiology, Army Medical College, Rawalpindi from March 2004 to February 2006. Thirty patients with systolic Pulmonary Artery Pressure (PAP) >50 mmHg on pre-operative echocardiography were inducted. Swan Ganz catheter was inserted to record baseline pulmonary artery pressure and pulmonary capillary wedge pressure (PCWP), while cardiac output (CO) was recorded through lithium dilution method. Pulmonary Vascular Resistance (PVR) was calculated with the help of a formula. Inhaled nitric oxide (iNO) was administered after the surgery and the same parameters were recorded again after one hour. Results: The majority of patients were females (73%), while males were only 27%. Out of 30, 21 had isolated mitral stenosis and 9 had mixed mitral and aortic valve disease. 22 patients responded significantly to iNO therapy with ‰¥40.0% reduction in their baseline PVR while 8 patients showed insignificant improvement in their PVR (663±233 dynes.sec.cm-5 to 605±222 dynes.sec.cm-5). Conclusion: Significant improvement in pulmonary vascular resistance in the responders and maintenance of high pressures despite iNO therapy in non-responders indicate that apart from some abnormality in nitric oxide pathway, some other factors may be a contributing in the causation of PH secondary to mitral stenosis in adults, which warrant further studies. Keywords: Nitric Oxide, mitral stenosis, pulmonary hypertension, pulmonary artery pressure, pulmonary vascular resistance